2019
DOI: 10.1016/j.jpsychores.2019.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis abuse and dependence in kidney transplant candidates

Abstract: Objective: Cannabis is the most commonly used non-alcohol intoxicant in the general population. There are no consistent guidelines on the implications of cannabis abuse and dependence (CAD) in kidney transplant candidates. The aims of this study were to characterize kidney transplant candidates with comorbid CAD and examine the implications of CAD on transplant candidacy. Method: This was a retrospective cohort study of kidney transplant candidates meeting diagnostic criteria for CAD at a tertiary center from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 9 publications
(10 reference statements)
1
21
0
Order By: Relevance
“…In kidney transplant candidates, cannabis abuse was associated with psychiatric comorbidities (24). Cannabis can cause behavioral changes, and movement disturbances, while higher doses inhibit movement and lower doses stimulate it (24). In our study, similarly, behavioral assessment revealed an increasing trend for anxiety level after 2 and 3 weeks following cannabis use.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In kidney transplant candidates, cannabis abuse was associated with psychiatric comorbidities (24). Cannabis can cause behavioral changes, and movement disturbances, while higher doses inhibit movement and lower doses stimulate it (24). In our study, similarly, behavioral assessment revealed an increasing trend for anxiety level after 2 and 3 weeks following cannabis use.…”
Section: Discussionsupporting
confidence: 71%
“…The fi rst report of cannabis allergy dates back to 1971 signifi cantly affected the quality of life (23). In kidney transplant candidates, cannabis abuse was associated with psychiatric comorbidities (24). Cannabis can cause behavioral changes, and movement disturbances, while higher doses inhibit movement and lower doses stimulate it (24).…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen studies reported the rates of illicit substance use in solid-organ transplant candidates ( Table 1). Seven studies reviewed retrospective data [13][14][15][16][17][18]22], three studies used crosssectional assessment [10,[25][26], one study analyzed the national transplant registry [23], one study utilized prospective study design [19], and one study used a survey [24] to collect data. The sample sizes of these studies ranged from 59 [16] to 52,689 [23].…”
Section: Illicit Substance Use Among Solid-organ Transplant Candidatesmentioning
confidence: 99%
“…Eight studies were on liver transplant, three on kidney transplant, and two on cardiac transplantation. Three studies primarily focused on cannabis use [13,23], one on injection drug use (IDU) [16], three studies did not present data on individual substances [18,[24][25], and the others presented data on multiple substances. In the overall cohort, any illicit drug was used by 35% at some point in time, most frequently cannabis (31%), amphetamine (16%), heroin (5%), cocaine, inhalants, and hallucinogens (8% each)…”
Section: Illicit Substance Use Among Solid-organ Transplant Candidatesmentioning
confidence: 99%
See 1 more Smart Citation